Long-term social recognition memory in zebrafish - Madeira, Natália (2017)
In species in which individuals live in stable social groups, individual recognition is expected to evolve to allow individuals to remember past interactions with different individuals and adjust future behavior toward them accordingly. Thus, social memory is expected to be a ubiquitous component of social cognition of social species. However, few studies have investigated the occurrence of social memory in non-mammals. Here we evaluated the ability of zebrafish (Danio rerio) to recognize different conspecifics and to retain this information in long lasting (i.e. 24 h) memories. We used a social discrimination paradigm, adapted from mouse studies, in which the focal individual meets two pairs of conspecifics in two consecutive days: one conspecific is the same in both days and the other is different between days 1 and 2. If animals have the ability to discriminate between different conspecifics, it is predicted that they will spend more time exploring the novel than the familiar (i.e. already seen in day 1) conspecific. In this study, zebrafish with access to both olfactory and visual conspecific cues exhibited consistent recognition of a previously encountered (familiar) conspecific after a 24 h delay. This result supports the hypothesis that long-term social memory, previously described in mammals, is also present in zebrafish, hence extending the evidence for the presence of this type of memory to teleost fish.